Orbital involvement in COVID-19 associated mucormycosis - Palle, Manasa; Narasaiah, Dhanapala; Raj Shivalingaiah, Pruthvi; Menon Premachandran, Architha; Gopi, Rahul; Vayalombron Mampally, Theerta; Kumari Chikkavenkataiah, Shwetha (International Journal of Research in Medical Sciences, 2023)
Background: Mucormycosis is an opportunistic, potentially lethal, fungal infection predisposed by uncontrolled diabetes mellitus, immunosuppressive therapy, primary or secondary immunodeficiency, injudicious use of corticosteroids, hematological malignancies, hematological stem cell transplantation, solid organ malignancies, solid organ transplantation. Rhino-orbital mucormycosis is the commonest form of mucormycosis. This study was done to discuss the management strategies (orbital decompression/clearance, orbital exenteration, retrobulbar amphotericin B) in the treatment of orbital mucormycosis and its clinical outcomes. Methods: A retrospective descriptive study was conducted between May 2021 and October 2021 at Bowring and Lady Curzon hospital, Shri Atal Bihari Vajpayee Medical College and Research Institute, Karnataka, India. 181 patients with post-COVID RTPCR negative rhino-orbital mucormycosis were included in the study. Patients underwent endoscopic orbital clearance, orbital exenteration based on the extent of orbital involvement. Results: 143 were males and 38 were females. 160 patients underwent orbital decompression and clearance of necrotic tissue. 21 patients underwent orbital exenteration. Final visual acuity of perception of light (PL) positive and above was achieved in 147 patients. 57/58 (98.27%) patients had improvement in extraocular movements post-surgery and resolution of diplopia after orbital decompression/clearance. Conclusions: Endoscopic orbital clearance helps to reduce the need for orbital exenteration in PL negative patients. TRAmB as adjuvant helps in decreasing the ocular morbidity. Orbital exenteration is best avoided, when possible, to avoid cosmetic disfigurement and psychological trauma to the patient.